let A, B be strict multMagma ; :: thesis: ( the carrier of A = product () & ( for f, g being Element of product ()
for i being set st i in I holds
ex Fi being non empty multMagma ex h being Function st
( Fi = F . i & h = the multF of A . (f,g) & h . i = the multF of Fi . ((f . i),(g . i)) ) ) & the carrier of B = product () & ( for f, g being Element of product ()
for i being set st i in I holds
ex Fi being non empty multMagma ex h being Function st
( Fi = F . i & h = the multF of B . (f,g) & h . i = the multF of Fi . ((f . i),(g . i)) ) ) implies A = B )

assume that
A17: the carrier of A = product () and
A18: for f, g being Element of product ()
for i being set st i in I holds
ex Fi being non empty multMagma ex h being Function st
( Fi = F . i & h = the multF of A . (f,g) & h . i = the multF of Fi . ((f . i),(g . i)) ) and
A19: the carrier of B = product () and
A20: for f, g being Element of product ()
for i being set st i in I holds
ex Fi being non empty multMagma ex h being Function st
( Fi = F . i & h = the multF of B . (f,g) & h . i = the multF of Fi . ((f . i),(g . i)) ) ; :: thesis: A = B
for x, y being set st x in the carrier of A & y in the carrier of A holds
the multF of A . (x,y) = the multF of B . (x,y)
proof
set P = product ();
let x, y be set ; :: thesis: ( x in the carrier of A & y in the carrier of A implies the multF of A . (x,y) = the multF of B . (x,y) )
assume that
A21: x in the carrier of A and
A22: y in the carrier of A ; :: thesis: the multF of A . (x,y) = the multF of B . (x,y)
reconsider x1 = x, y1 = y as Element of product () by ;
[x1,y1] in [: the carrier of A, the carrier of A:] by ;
then reconsider f = the multF of A . [x1,y1] as Element of product () by ;
[x1,y1] in [: the carrier of B, the carrier of B:] by ;
then reconsider g = the multF of B . [x1,y1] as Element of product () by ;
A23: dom () = I by PARTFUN1:def 2;
then A24: dom g = I by CARD_3:9;
A25: for i being object st i in I holds
f . i = g . i
proof
let i be object ; :: thesis: ( i in I implies f . i = g . i )
assume A26: i in I ; :: thesis: f . i = g . i
then A27: ex Gi being non empty multMagma ex h2 being Function st
( Gi = F . i & h2 = the multF of B . (x1,y1) & h2 . i = the multF of Gi . ((x1 . i),(y1 . i)) ) by A20;
ex Fi being non empty multMagma ex h1 being Function st
( Fi = F . i & h1 = the multF of A . (x1,y1) & h1 . i = the multF of Fi . ((x1 . i),(y1 . i)) ) by ;
hence f . i = g . i by A27; :: thesis: verum
end;
dom f = I by ;
hence the multF of A . (x,y) = the multF of B . (x,y) by ; :: thesis: verum
end;
hence A = B by ; :: thesis: verum